TEMPERAMENT DETERMINATION FOR MELATONIN: A BRIDGE FROM IRANIAN TRADITIONAL TO MODERN SLEEP MEDICINE - Minae, Mohammad B; Soltani, Seyedshahin; Besharat, Mehdi; Karimi, Foruzan; Nazem, Esmaeil (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
History acknowledged Ibn Sina, or Avicenna, the author of the highly skilled textbook of medicine "Al-Qanun Fi Al-Tibb" or "The Canon of Medicine", as one of the greatest physicians in medicine. According to this medical textbook, the explanation of the existence of a cold temperament for sleep was that during sleep hours, people tended to have a movement of the nature of the body toward the inside, which caused the body to become cold during sleep. Temperament determination for molecules, including drugs, has proved several applications. The present study tried to demonstrate that the multitasking melatonin molecule, as a sleep related hormone, had a cold temperament. The consideration of this temperament for melatonin had the potential to connect and integrate Iranian traditional medicine to current medicine, and also opened new frontiers for the physiopathology of modern sleep medicine, based on traditional medicine.